2016
DOI: 10.1177/0363546516630977
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of Autologous Cartilage Chips Improves Cartilage Repair Tissue Quality in Osteochondral Defects

Abstract: This study substantiates the chondrogenic role of cartilage chips in osteochondral defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Compared with dogs and other smaller animal models, the size, weight requirements and cartilage thickness of pigs are much closer to those of humans, and they are physiologically and physically similar to us, and the cartilage defect repair process of pigs may be closer to that of humans. Therefore, this study is of high clinical reference value [29][30][31][32].…”
Section: Discussionmentioning
confidence: 94%
“…Compared with dogs and other smaller animal models, the size, weight requirements and cartilage thickness of pigs are much closer to those of humans, and they are physiologically and physically similar to us, and the cartilage defect repair process of pigs may be closer to that of humans. Therefore, this study is of high clinical reference value [29][30][31][32].…”
Section: Discussionmentioning
confidence: 94%
“…In a minipig model, defects treated with autologous bone fragments and cartilage chips had significantly more hyaline and fibrocartilage than defects treated with bone fragments alone, although no difference was noted in the bone defect volume between the groups at 6 or 12 months. 71…”
Section: Methodsmentioning
confidence: 99%
“…Gotterbarm et al [25] showed that 6.3 mm diameter OCD did not spontaneously heal in mini-pig, confirming the applicability of this pig breed to articular cartilage research. e large majority of the cartilage regeneration studies in the mini-pig are performed on the joint knee, involving the medial [66] or femoral condyles [67,68], or femoral trochlea. Generally, 6 mm to 8 mm diameter or larger dimensions OCD are created, and the postoperative follow-up period is usually between 3 and 24 months (Table 5).…”
Section: Pigmentioning
confidence: 99%
“…Several studies on cartilage and cartilage defects have been reported using min-pig. Christensen and coauthors [68] created OCD of 6 mm diameter and 8 mm depth in the medial trochlear to investigate the role of cartilage chips. ey found that the cartilage chips promoted the formation of fibrocartilage rather than fibrous tissue.…”
Section: Applications Of Pig Ocd Models For Testing Of Osteochondral mentioning
confidence: 99%